Typological Features of Temperament and Properties of the Nervous System of Athletes of Team Sports (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Modern sports training puts before athletes the need to overcome extremely difficult, and in some cases, exorbitant psychoemotional and physical stress, especially in the competitive period. This article discusses the temperament properties of athletes involved in football and basketball. The study involved 60 athletes (30 football players and 30 basketball players) of boys and youths aged 14-16 years. The testing technique assumed the identification of types of higher nervous activity, as well as the influence of temperamen on sports activities. It has been established that choleric athletes of both groups are typical extroverts, phlegmatic people are characterized by traits of an introverted personality type, and sanguine people occupy an intermediate position. Since the temperament of a person is directly related to the features of the nervous system, the study of psychology in groups of athletes becomes necessary. Influence of typological features of manifestation of properties of nervous system on strong-willed qualities (patience, persistence) of athletes [1].